Seroprevalence of antibodies against Chlamydia trachomatis and enteropathogens and distance to the nearest water source among young children in the Amhara Region of Ethiopia. - Kristen Aiemjoy; Solomon Aragie; Dionna M Wittberg; Zerihun Tadesse; E Kelly Callahan; Sarah Gwyn; Diana Martin; Jeremy D Keenan; Benjamin F Arnold (PLoS Neglected Tropical Diseases, 2020)
The transmission of trachoma, caused by repeat infections with Chlamydia trachomatis, and many enteropathogens are linked to water quantity. We hypothesized that children living further from a water source would have higher exposure to C. trachomatis and enteric pathogens as determined by antibody responses. We used a multiplex bead assay to measure IgG antibody responses to C. trachomatis, Giardia intestinalis, Cryptosporidium parvum, Entamoeba histolytica, Salmonella enterica, Campylobacter jejuni, enterotoxigenic Escherichia coli (ETEC) and Vibrio cholerae in eluted dried blood spots collected from 2267 children ages 0-9 years in 40 communities in rural Ethiopia in 2016. Linear distance from the child's house to the nearest water source was calculated. We derived seroprevalence cutoffs using external negative control populations, if available, or by fitting finite mixture models. We used targeted maximum likelihood estimation to estimate differences in seroprevalence according to distance to the nearest water source. Seroprevalence among 1-9-year-olds was 43% for C. trachomatis, 28% for S. enterica, 70% for E. histolytica, 54% for G. intestinalis, 96% for C. jejuni, 76% for ETEC and 94% for C. parvum. Seroprevalence increased with age for all pathogens. Median distance to the nearest water source was 473 meters (IQR 268, 719). Children living furthest from a water source had a 12% (95% CI: 2.6, 21.6) higher seroprevalence of S. enterica and a 12.7% (95% CI: 2.9, 22.6) higher seroprevalence of G. intestinalis compared to children living nearest. Seroprevalence for C. trachomatis and enteropathogens was high, with marked increases for most enteropathogens in the first two years of life. Children living further from a water source had higher seroprevalence of S. enterica and G. intestinalis indicating that improving access to water in the Ethiopia's Amhara region may reduce exposure to these enteropathogens in young children.